Pengaruh Cognitive Image dan Unique Image terhadap Resivit Intention melalui Visitor Engangement Gunung Tangkuban Parahu - Rafi'ul Huda, Muhammad; Yadi Ernawadi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of cognitive image and unique image on revisit intention through visitor engagement at the Mount Tangkuban Parahu tourist destination. The research method used was a survey with a quantitative approach. Data were collected using a questionnaire distributed to 140 domestic tourists who had visited Mount Tangkuban Parahu at least once in the past year. Data were then analyzed using Partial Least Squares (PLS) using the SmartPLS application. The results showed that cognitive image had a direct and significant effect on revisit intention, while unique image did not have a direct and significant effect on revisit intention but did significantly influence visitor engagement. Furthermore, visitor engagement had a positive and significant effect on revisit intention and acted as a mediating variable in the relationship between unique image and revisit intention. The conclusion of this study is that tourists' positive perceptions of destination attributes, particularly uniqueness and emotional engagement during their visit, are important factors in encouraging tourists' desire to return to Mount Tangkuban Parahu.   Keywords: Cognitive Image, Unique Image, Visitor Engagement, Revisit Intention